Sprawność funkcjonalna pacjentów w podeszłym wieku hospitalizowanych w oddziałach neurologicznych - Fidecki, Wiesław; Wysokiński, Mariusz; Wrońska, Irena; Kulina, Dorota; Weremkowicz, Iwona; Kędziora-Kornatowska, Kornelia; Sienkiewicz, Zofia; Zalewski, Andrzej; Jakubowska, Klaudia; Kuszplak, Kamil (Pielęgniarstwo Neurologiczne i Neurochirurgiczne, 2017)
Introduction. Functional efficiency of the elderly can be defined as the ability to perform ordinary daily life tasks safely and independently. Aim. The research aims at determining the functional efficiency of elderly patients hospitalized in neurological departments. Material and Methods. The study was performed in 113 elderly patients hospitalized in neurological departments of hospitals in the city of Lublin. The research material was collected using two standardized tools: the Barthel index and the Katz index (ADL). Results. When evaluating patients with the Barthel index, 38.00% of patients were assigned to category I; 52.20% to category II and 9.80% to category III. In the ADL scale, 68.10% of the respondents were fully functioning, 12.40% were moderately functioning, and 19.50% were disabled. Conclusions. The study group of elderly patients in neurological departments exhibited moderate functional impairment. Age significantly differentiated the functional abilities of the research group. Education influenced the degree of independence in neurological patients. (JNNN 2017;6(3):102–106)